CRIMINAL RESPONSIBILITY FOR TERRORISM - Else, Angelina (Administrative and Criminal Justice, 2021)
Acts of terrorism often result in fatalities, but the impact of terrorism is not limited to loss of lives. Terrorism acts can disturb or suspend the peace process; they cause, lengthen, or deepen conflicts and escalate violence. In addition, terrorism has an effect on the economy of the state, given that combatting of terrorism requires significant temporal and financial resources.The threat posed by international terrorism not only constitutes one of the biggest challenges that the world and Europe in particular is currently facing, but also affects the security and economic interests of the Latvian nationals. In addition, terrorism-related crimes threaten the security of not only separate states, but that of the entire international community as well.In the view of the author, the relevance of the topic is illustrated by the fact that 23 May 2018, saw the Criminal Act of Latvia being complemented by a new (IX1) section on “Crimes Related to Terrorism”, thereby underscoring the preparedness of Latvia to adjust its legislative framework in order to avert possible threats of terrorism. The new version of the law sees terrorism, financing of terrorism, invitation to terrorism and terrorism threats, recruitment and training of persons for terrorism, travelling for terrorism purposes, and justification of terrorism classified as criminal offences.Author has chosen the topic of terrorism with the aim of exploring the definition of terrorism and its depiction in international and Latvian law, as well as analysing the criminal liability for terrorism prescribed by the Latvian law and determining the issues associated with the classification of terrorism.The paper consists of introduction, three chapters, and conclusion. In the first chapter, the definition of terrorism is considered. The second chapter is devoted to the analysis of criminal liability for terrorism under the Latvian law, and the third chapter – to the issues associated with the classification of terrorism. Finally, conclusions with respect to the threats posed by terrorism to the European Union and Latvia are drawn.